Utilización de rayos gamma en alfalfa (Medicago sativa) en condiciones tropicales - Campi Amaiquema, Karla Rommyna (2022)
Alfalfa (Medicago sativa) is the main forage for milk production worldwide; among cultivated forages, legumes of the Medicago genus are the most widely used. Alfalfa, due to its high yield and content in protein, vitamins, minerals (especially calcium) and fiber percentage, is of high quality for milk production; in addition, it helps to improve the soil due to its potential to restore atmospheric nitrogen in association. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the use of gamma rays in alfalfa (Medicago sativa) in tropical conditions. From the above, it was determined that alfalfa (Medicago sativa L.) is the maximum perennial forage crop, due to its production, forage exceptionality and version to exclusive environments. The great variety of environments and cultivars in which it is grown determines the surprising variations in its production. The application of gamma rays generates free radicals, which can damage or alter cellular components exclusive to grass plants, also generating changes within the morphology, anatomy, biochemistry and body structure. Within the germination power of alfalfa Nacional plants and alfalfa Granada Mejorada, they present the same behavior when sown in soil and newspaper, which is related to the fact that the lower the temperature, the higher the germination percentage. The agronomic behavior of the alfalfa Granada Mejorada is superior to the alfalfa Nacional in the control treatment while in the treatment with mutagenics in terms of germination and agronomic behavior, alfalfa Nacional has better results.